Akibat Hukum Akta Hibah Yang Dibuat oleh PPAT Tanpa Persetujuan Ahli Waris Lainnya - Putra, I Putu Angga Suwidya; Novy Purwanto, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024), 2024)
This research aims to understand the legal consequences of a grant deed made by a Notary (PPAT) without the consent of the remaining grant recipients. This research uses normative research methodology because it specifically investigates uncertainty in legal standards. This lack of clear norms arises due to confusion in statutory regulations regarding the requirements for an heir certificate in the process of granting grants. This research uses primary data sources, including statutory regulations, court decisions, legal theories, ideas and perspectives of legal professionals. This research methodology includes a legislative approach and a conceptual approach. The results of this research indicate that the legal consequence of a gift deed that does not receive approval from the heirs is legal invalidity. PPATs who draw up gift deeds without the consent of the heirs risk facing administrative and civil sanctions, especially if this causes losses for the parties involved.